THE EFFECT OF MOBILE ACCESS (AUDIO VISUAL EASY LEARN ENGLISH) ON STUDENTS’ VOCABULARY ACHIEVEMENT AT SMPN 11 KENDARI - Veronica, Eva; Mursalim, Mursalim (Universitas Halu Oleo, 2019)
The objective of this study is to find out the effect of using mobile access (Audio Visual Easy Learn English) on students’ vocabulary achievement at SMPN 11 Kendari. Mobile Access (Audio visual easy learn English) as a media in learning teaching process. This research used quasi experimental design, the population is all seventh- grade students, and the sample is class VII1 as the experimental group and VII2as control group. The experimental group consisted of 30 students and control group consisted of 21 students. The research instrument consisted of 44 questions of vocabulary test. To collect the data, the researcher gave pre-test, taught by using Mobile Access (Audio Visual Easy Learn English), and giving post-test. Mean score of post-tests (79.63) in experimental class is higher than pre-test score (59.66). While, in control class also has improvement but not too significant. It can be seen on post-test score (64.80) is higher than pre-test score (55.19). Based on the calculation of T-test, it shows that tcount = 3.775, while t-table =2.010 at level of = 0.05 with DF = 49. It means that tcount is higher than table, Therefore H0 was rejected and H1 was accepted. This can be concluded that there was a significant effect of using a significant effect using Mobile Access (Audio Visual Easy Learn English) on students’ vocabulary achievement at the seventh-grade students of SMPN 11 Kendari. Keywords: MA, Mobile Access, Audio Visual Easy Learn English, vocabulary achievement